Modelling physical processes in higher plants using leaf replicas for space applications - Kuzma, Joanna; Poulet, Lucie; Fontaine, Jean-Pierre; Dussap, Claude-Gilles (Comptes Rendus. Mécanique)
In the future, higher plant cultivation will be a key component of Bioregenerative Life-Support Systems. This will require a deep understanding of phenomena that play an important role at the core of plant metabolism and of their interaction with the environment. Plants are complex organisms that must be studied with the use of leaf replicas. This enables the study of physical phenomena at the leaf surface, without biochemical or biological interactions nor genetic variability. To assess the influence of gravity, it is a necessary step to develop precise mechanistic models of plant behaviour in space. This review article presents the state-of-the-art of leaf replicas and concomitant phenomena, with a space gaze.